Synthesis and reactivity of a beta-diketiminate Sm-II complex - Van Velzen, Niels J. C.; Harder, Sjoerd (Australian Journal of Chemistry, 2022)
Attempts to stabilise a Tm-II metal centre with the bulky beta-diketiminate ligand HC[C(Me)=N (DIPP)](2) (BDI) failed (DIPP, 2,6-diisopropylphenyl). Reaction of TmI2 and 2 equiv. (BDI)K gave the Tm-III complex (BDI)(BDI-H)Tm (I) in which (BDI-H)(2-) is a doubly deprotonated ligand. However, following the same route, (BDI)(2)Sm (2) was isolated in 48% crystalline yield. Complex 2 is highly soluble in aromatic solvents or alkanes and was reacted with various reagents like phenazine, PhSSPh, O-2, NO, cuminil and fluorenone. This led to isolation and structural characterisation of the following Sm-III complexes: [(BDI)(2)Sm](2) (mu-phenazine) (3), [(BDI)Sm(SPh)(mu-SPh)](2) (4), (BDI)(BDI-H)Sm (5a), (BDI)(2)Sm(OC13H8) (6) and (BDI)(2)Sm(NO2) (7). The rich redox reactivity of (BDI)(2)Sm (2) and its very high solubility in apolar solvents like hexane make it an attractive reducing agent in synthesis.
CRIS-Team WoS Importer:2022-03-18